Interview with Prof. Kgothatso B. Shai, University of Limpopo, South Africa Afrocentric Epistemology for Social Sciences - Kgothatso B. Shai (Ученые записки Института Африки Российской академии наук)
Kgothatso Shai is a Full Professor of Political Science and the immediate past Head of the Department of Cultural & Political Studies at the University of Limpopo in South Africa. He previously served as President of the South African Association of Political Studies (SAAPS). He is also the incumbent President of the South African Association of Public Administration and Management (SAAPAM), where he is also serving as the founding Editor in Chief of the association’s flagship Book Series. He is a National Research Foundation (NRF)-rated researcher and the author of three academic books. He has published over 100 peer-reviewed and Department of Higher Education and Training (DHET)-accredited journal articles and book chapters. His research interests interweave between African politics, international relations, and the politics of knowledge.